Meta‐analysis of direct‐to‐surgery lateral pelvic lymph node dissection for rectal cancer. (18th May 2021) - Cribb, Benjamin; Kong, Joseph; McCormick, Jacob; Warrier, Satish; Heriot, Alexander
Abstract: Aim: Direct‐to‐surgery rectal resection with lateral pelvic lymph node dissection (LPLND) is a treatment strategy commonly employed in Japan to improve oncological outcomes for rectal cancer. The aim of this study was to assess oncological outcomes in the literature for patients with low rectal cancer who underwent direct‐to‐surgery resection and LPLND compared with those who underwent total mesorectal excision (TME) alone. Method: A literature search of Medline, Embase and PubMed databases was performed to identify relevant studies published between 1989 and 2020. The primary outcomes were 5‐year overall survival (OS) and 5‐year disease‐free survival (DFS). The secondary outcomes were cancer recurrence (local, distant and total) and operative burden (operative time and blood loss). Pooled relative risk (RR) of oncological outcomes was performed using the DerSimonian–Laird method random‐effect model. Results: Twenty‐one studies fulfilled inclusion criteria, including 19 nonrandomized studies of interventions and two studies from one randomized controlled trial. No differences were observed in 5‐year OS or 5‐year DFS. Local recurrence in nonrandomized studies was worse in patients who underwent LPLND [RR 1.41 (95% CI 1.21–1.64, p < 0.001)], as was total recurrence [RR 1.44 (95% CI 1.25–1.67, p < 0.001)]. No differences were observed for distant recurrence. Conclusion: In the published literature, direct‐to‐surgery resection with LPLND was associated with worse local and total recurrence. These predominantly nonrandomized data suggest that a nonselective approach to LPLND does not provide optimal management in radiotherapy‐naïve patients with low rectal cancer. Further prospective randomized studies with a focus on patient selection are required.